La psicología en la escritura: una visión general - Gil Escudero, Guillermo (1985)
In this paper, after a short introduction which considers the nature and importance of writing, the main ideas about the study of its development, from a historical perspective as well as from an ontogenetical point of view, are exposed. A classification of the different topics of the psychological study of writing is proposed. Finally, a feasible integrative framework of the areas of study on writing from a cognitive perspective is offered.